Treatment of advanced rectal cancers: Cylindrical abdominoperineal excision of rectum - Lamichhane, Nirmal; Walker, Kenneth G. (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Treatment for patients with locally advanced low lying rectal cancer differs significantly from patients with rectal cancer restricted to the mesorectum. They require multimodality treatment, including preoperative chemo-radiation and extended surgical resection. Cylindrical abdominoperineal excision of rectum (C-APER) along with possible composite pelvic organ resection is a surgical method to remove an adequate circumferential margin. Method: Patients with the diagnosis of advanced rectal cancers over a period of 9 months are included in this study. Therapeutic approach of C-APER is taken for these patients with focus on multimodality treatment protocols to downstage the tumours and extended resections to enable complete removal of all tumour tissue with clear surgical margins. Consecutive review of cases of advanced rectal cancer to their immediate surgical outcome were done. Results: Five patients with compromised CRM in MRI of rectum, 4 were treated with Neoadjuvant FOLFOX 6 regimen chemotherapy 3 cycles and Short course Radiotherapy. All underwent surgery 6-8 weeks after treatment. The pelvic floor was repaired with biological mesh in 1 and synthetic mesh in 4. The pathological stage of disease remained T3 and above despite neoadjuvant treatment in majority of patients but none of them had positive CRM. The wound complication rates were high in the perineum with serous discharge in almost every patient and one patient needing long term vacuum assisted dressing in the community. Conclusion: The surgery is technically feasible with acceptable morbidity in short term with possible long term outcome of reduced loco-regional failure.